Koli woman wearing a Thauja with a pendant featuring the double fish motif - Mumbai Archive Project Team (Jio Institute, 2024)
Married women wear thauja, a thick mangalsutra (necklace) with multiple strands of black beads, typically consisting of five or nine strands. The woman in the picture is wearing a thauja with a pendant featuring the double fish motif, symbolic of the fishing livelihood of Kolis.